Efficiency of Women Agricultural Labourers in Rice Farming Systems of Kerala and Tamil Nadu - T. Rajula Shanthy (Indian Res. J Ext. Edu., 2009)
The study was conducted in Kollam district of Kerala and Kanyakumari district of Tamil Nadu. A labour efficiency scale was developed by functional approach and the same was used to measure the labour efficiency of women agricultural labourers. Using cluster analysis, the items were grouped into different dimensions and labeled based on the content of the items. In general, majority (63%) of the women agricultural labourers were low in labour efficiency. The analysis revealed significant difference between the women agricultural labourers of Kerala and Tamil Nadu with respect to their overall labour efficiency level. The difference was mainly due to labour attachment practices and increasing demand for non-agricultural works. Dimension-wise analysis of labour efficiency showed that majority of them belonged to the high group under the dimension adjustability and competency, whereas majority had low efficiency with respect to dimensions such as determination in work situation, inter-personal relationship, team spirit, commitment, work environment, socio-economic and situational. The respondents were observed to have neither high nor low efficiency in case of confidence dimension.